Expression of phosphorylated Hippo pathway kinases (MST1/2 and LATS1/2) in HER2-positive and triple-negative breast cancer patients treated with neoadjuvant therapy. Issue 5 (4th May 2017) - Ercolani, Cristiana; Di Benedetto, Anna; Terrenato, Irene; Pizzuti, Laura; Di Lauro, Luigi; Sergi, Domenico; Sperati, Francesca; Buglioni, Simonetta; Ramieri, Maria Teresa; Mentuccia, Lucia; Gamucci, Teresa; Perracchio, Letizia; et al.
ABSTRACT: The Hippo kinases MST1/2 and LATS1/2 inhibit the oncoproteins TAZ/YAP and regulate T cell function. Hippo kinases also cooperate with the ATR-Chk1 and ATM-Chk2 pathways, central orchestrators of the DNA damage response (DDR). We hypothesized that MST1/2 and LATS1/2 localization differently impacts the efficacy of neoadjuvant therapy (NAT) in breast cancer, being protective when expressed in the cytoplasm of tumor cells and in tumor-infiltrating lymphocytes, whereas representing molecular determinants of chemoresistance when present in the nucleus as a consequence of their cooperation with the DDR. Diagnostic biopsies from 57 HER2-positive and triple-negative breast cancer patients treated with NAT were immunostained for evaluating the expression of phosphorylated MST1/2 (pMST1/2) and LATS1/2 (pLATS1/2) in tumor-infiltrating lymphocytes (TILs) and in cancer cells. TAZ and Chk1 immunostaining was exploited for investigating subcellular compartment-dependent activity of Hippo kinases. Nuclear pMST1/2 (pMST1/2 nuc ) expression was significantly associated with nuclear expression of Chk1 (p = 0.046), whereas cytoplasmic pMST1/2 (pMST1/2 cyt ) expression was marginally associated with cytoplasmic TAZ staining (p = 0.053). Patients whose tumors expressed pMST1/2 nuc were at increased risk of residual disease after NAT (pCR ypT0/is ypN0: OR 4.91, 95%CI: 1.57–15.30; pCR ypT0 ypN0: OR 3.59, 95%CI 1.14–11.34). Conversely, exclusive cytoplasmic localization of pMST1/2 (pMST1/2 cyt )seemed to be a protective factor (pCR ypT0/is ypN0: OR 0.34, 95%CI: 0.11–1.00; pCR ypT0 ypN0: OR 0.31, 95%CI 0.10–0.93). The subcellular localization-dependent significance of pMST1/2 expression suggests their involvement in different molecular networks with opposite impact on NAT efficacy. Larger studies are warranted to confirm these novel findings.